Río Bec. Des grandes maisons et des récoltes - Marie-Charlotte Arnauld; Dominique Michelet; Chloé Andrieu; Alfonso Lacadena; Éva Lemonnier; Boris Vannière; Philippe Nondédéo; Julie Patrois (Journal de la Société des Américanistes)
In the Río Bec region, archaeological, iconographic and epigraphic data indicate that kingship has been weakly articulated from AD 550 to 950. Sub-royal elites were active, creating highly visible houses with land domains that served factional strategies and, late in time, diffused architectural ideas over a wide area. The picture is one of a highly fragmented society consisting of many economically autonomous agents, each pursuing corporate interests that combined intensive staple production and auto-construction of stable residences on their land, with minimal insertion in craft production and regional exchanges.